2012
DOI: 10.1016/j.kjms.2011.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Mood stabilizers for the treatment of behavioral and psychological symptoms of dementia: An update review

Abstract: Behavioral and psychological symptoms of dementia (BPSD) are common and debilitating problems, but current treatments are limited. Antipsychotic agents show some efficacy on BPSD, but their use is limited by the associated risk of cerebrovascular events and mortality. Reports have shown the efficacy of mood stabilizers on BPSD, but systemic reviews on this issue are scant. This article aims to review studies of the efficacy of mood stabilizers on BPSD, and the quality of the available evidence. We searched for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Two of three trials utilising carbamazepine in the treatment of BPSD suggested improved outcomes . Concerns regarding the tolerability of carbamazepine limit its use.…”
Section: Specific Drug Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of three trials utilising carbamazepine in the treatment of BPSD suggested improved outcomes . Concerns regarding the tolerability of carbamazepine limit its use.…”
Section: Specific Drug Classesmentioning
confidence: 99%
“…Reviews have failed to find evidence that valproate helps BPSD . One trial revealed poorer behavioural outcomes, and almost all reported more adverse events in the treatment groups …”
Section: Specific Drug Classesmentioning
confidence: 99%
“…(Note that, although valproic acid [Depakote] and other anticonvulsant mood stabilizers are sometimes used, there are currently little or no data supporting their use and we do not recommend using anticonvulsants in this setting [for review see Yeh & Ouyang, 2012]. (Note that, although valproic acid [Depakote] and other anticonvulsant mood stabilizers are sometimes used, there are currently little or no data supporting their use and we do not recommend using anticonvulsants in this setting [for review see Yeh & Ouyang, 2012].…”
Section: Box 24-5 Strategies For Treating Insomnia In Dementiamentioning
confidence: 99%
“…Although there is some literature that suggests that Sodium Valproate is helpful in treating BPSD [50], recent reviews question the efficacy and tolerability of Sodium Valproate in BPSD [51]. Konovalov, Muralee [52] suggest that anticonvulsant mood stabilizers should not be recommended for routine use in the treatment of BPSD citing that of 7 RCTs of anticonvulsant therapy in BPSD published only one showed significant improvement compared to placebo, while five showed no statistical difference and one showed significant worsening of BPSD in the treatment group compared to placebo.…”
Section: Medicationmentioning
confidence: 99%